Types of Fish Found in Peat Swamp Waters in Sontang Village, Bonai Darussalam District, Rokan Hulu Regency, Riau Province. - Kurniawan, Ahmad Jati; Eddiwan, Eddiwan; Putra, Ridwan Manda (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTPeat swamp waters in Sontang Village are inhabited by many fish species. To understand the types of fish in the peat swamp waters, this research was carried out, which was carried out in May 2019. Sampling was conducted three times, using fishing rods, nets and fish traps. Fish that have been caught then identified. The results show that there are 3 orders, 12 families and 19 species of fish that live in the peat swamp waters. The types of fish include Rasbora argyrotaenia, Thynnichthys polylepis, Hampala macrolepidota, Anabas testudineus, Helostoma teminckii, Channa Lucius, Channa. Striata, Channa micropeltes, Trichogaster trichopterus, Belontia hasselti, Oxyeleothris marmorata, Pristolepis grooti, Mastocellus erythrotaenia, Oreochromis niloticus, Mystus nemurus, Mystus nigriceps, Clarias batrachus, Crypypusterpuster.The most common fish species belong to the Perciformes order.Keywords: Peat swamp waters, Sontang village, Endemic peat swamp species